Clinical pharmacist interventions in patients with mental health disorders - Angela Bozhinoska; Dragana Dimkovic; Faton Veseli; Aleksandra Kapedanovska Nestorovska; Kristina Mladenovska (Makedonsko Farmacevtski Bilten)
Despite positive evidence for the impact of clinical pharmacy interventions on patients’ health outcome, the benefits of clinical pharmacist placed within multidisciplinary psychiatric team are still not recognized in our country. The aim of the present study was to highlight the role of clinical pharmacists in our healthcare system and evaluate the extent to which they contribute in reducing the incidence of medication-related problems (MRPs). The study included total of 82 patients hospitalized at the Department of Psychiatry at the Prilep General Hospital it the period from October 2022 to October 2023. MRPs were recognized in 70 (85.36%) patients. MRPs categories associated with medication selection (34.74%) and medication safety (16.43) followed by drug monitoring (14.55%) and patient compliance (14.08%) were found most prevalent. Clinical pharmacist made 213 recommendations (3.04 per patient). Most frequently recommended clinical interventions referred to: monitoring of laboratory parameters (9.86%), adherence to the pharmacotherapy (8.45%), prevention of use of too many medications for non-existing indication(s) or for a certain indication (7.98%) and recommendations for temporary or permanent discontinuation of medication (7.51%). Nearly 58% of all clinical pharmacist interventions aimed at preventing complications and morbidity that could arose from MRPs, of which 35% were graded as major in severity. The psychiatrists accepted 90.61% (193 of 213) of the suggested recommendations. Our findings highlight the opportunity for more targeted approaches to identifying and managing MRPs in tertiary care where tailored clinical pharmacist-led interventions may be of value. Implementation of clinical pharmacist led services, such as medication therapy management (MTM), in routine clinical practice can have a positive impact on the efficient and safe use of medicines in this patient’s group.